Collisional broadening and pressure shift of the potassium resonance doublets by nitrogen, helium, and hydrogen at high temperatures. (June 2022) - Ding, Yiming; Vandervort, Joshua A.; Freedman, Richard S.; Strand, Christopher L.; Marley, Mark S.; Hanson, Ronald K.
Highlights: Used KCl salts as precursors of K in a shock tube for TDLAS line shape measurements. Presented the K D1 and D2 profiles perturbed by N2, He, and H2 at high temperatures. Constructed power-law correlations of line shape parameters between 1100 – 1900 K. Found large discrepancies between the N2 results and existing experimental data. The He and H2 results showed good agreement with previous data and predictions. Abstract: This paper presents measurements of collisional broadening and pressure shift parameters for the potassium D1 and D2 transitions near 0.77 μ m with the collisional partners of molecular nitrogen, helium, and molecular hydrogen. Experiments were conducted in a shock tube at temperatures from 1100 K up to 1900 K, using tunable diode laser absorption spectroscopy and KCl salts as precursors of atomic potassium. In many of the experiments, the target gas was blended with argon to increase the ratio of the driver to driven gas speed of sound. This approach was employed to generate strong incident and reflected shock waves with sufficient temperature rises to produce optimal potassium concentrations (1–10 ppb) in the test gas for high signal-to-noise ratio absorption line shape measurements. The well-resolved absorption line shapes were modeled as Voigt profiles and a least-squares fitting algorithm yielded multiple variables, including the potassium concentration, the collisional full half-widths, and the pressure-induced shifts. Any broadening and shift contributions from the argon dilution were subtracted from the measurements using previous correlations. The pressure-normalized results, i.e., collisional broadening coefficients and pressure shift coefficients, are presented as temperature-dependent power-law relations for the species of interest. The helium and hydrogen results show good agreement with lower-temperature experimental data within 15–20%, and high-temperature theoretical predictions within 10–30%. However, larger discrepancies are observed between the nitrogen results and existing low-temperature experimental data and simplified impact theory predictions. These results may suggest that a more detailed model for the nitrogen collisional broadening of potassium is warranted. The presented correlations may also be useful for the development of potassium-based sensing methods with application to combustion, hypersonics, and astrophysics.